MORPHOLOGICAL CHANGES IN THE LIVER IN RATS IN THE STATE OF EXPERIMENTAL STRESS, BORN AT DIFFERENT PERIODS (International Conference on Educational Discoveries and Humanities, 2025)
Despite numerous evidence showing deviations of various immunological parameters characterizing the functional state of individual cell populations of the immune system during stress response, to date, quantitative analysis of structural and functional changes of the thymus and talok from lymphoid organs has not been carried out in the cross section of generations.